Recanalization and Functional Outcome in Patients with Cervico-cephalic Arterial Dissections. (11th May 2023) - Wadhwa, Ankur; Almekhlafi, Mohammed; Menon, Bijoy K.; Demchuk, Andrew M.; Bal, Simerpreet
ABSTRACT: Background: Cervico-cephalic arterial dissections (CeAD) are an important cause of stroke in young patients. This study aimed to determine the frequency and predictors of recanalization in spontaneous CeAD and to study the effect of recanalization on functional outcomes. Methods: We identified patients presenting with acute ischemic stroke secondary to CeAD from the CT angiography (CTA) database of the Calgary Stroke Program. Dissections were diagnosed based on standard clinical and imaging findings. At the discretion of treating stroke Neurologists, the patients were either treated with single antiplatelet or dual antiplatelet or triple therapy. Follow-up imaging with CTA, magnetic resonance imaging, and DSA was completed, and a Modified Rankin scale (mRS) was performed to determine the outcome. Results: Fifty-six patients with CeAdD were studied. Thirty-four patients (18 VAD; vertebral artery dissection and 16 CAD; carotid artery dissection) were followed up for recanalization. Complete recanalization was observed in 27 subjects; 13 patients with VAD recanalized in comparison to 14 with CAD (p = 0.40). All non-recanalized patients had hypertension. A good clinical outcome (mRS ≤ 2) was observed in 47 patients. Interestingly, the likelihood of a good neurological outcome was not influenced by recanalization status. There was no difference in clinical outcome for different sites in VAD, whereas patients with intracranial CAD had severe strokes (NIHSS > 21). Conclusions: CeAD has good recanalization rates and neurological outcomes, with recanalization seen even in vessels with initial complete occlusion. The presence of hypertension may influence recanalization. The efficacy of dual antiplatelets and heparin for early recanalization needs to be assessed in future clinical trials.